Exploring the Factors That Influence the Intention to Co-create Open Educational Resources: A Social Exchange Theory Perspective - Wang, Xiaochen; Han, Ruisha; Yang, Harrison Hao (Frontiers in Psychology, 2022)
Purpose – Based on social exchange theory, this study aimed to investigate, from the cost-benefits perspective, the intention to co-create open educational resources (OER). Design/methodology/approach – Participants in the study included 311 undergraduate students selected from those enrolled in a course on the China University MOOC platform. Regression analysis was conducted to examine cost and benefits factors that influenced participants’ intentions to co-create OER. Findings – 1) From the perspective of benefits, expected reciprocity, increase in knowledge self-efficacy, and creative self-efficacy were found to significantly and positively impact the intention to co-create OER, while increase in internet self-efficacy was not. 2) From the perspective of cost, perceived effort and perceived privacy were found to significantly and negatively impact the intention to co-create OER, while perceived intellectual property risks were not significant. Originality/value – Three strategies are recommended to promote the intention to co-create OER based on the findings of this study: 1) focusing on OER communities and developing reciprocity norms; 2) popularizing and promoting knowledge and use of Creative Commons copyright licenses; 3) providing easy-to-use online resource editing tools for use with OER repositories. Research limitations/implications – Future research should explore other ages, cultural backgrounds, and types of online learning experience to help broaden the universality of the results.